2007
DOI: 10.1657/1523-0430(2007)39[200:atargi]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Treeline and Retreating Glaciers: Implications for Conservation in Yunnan, P.R. China

Abstract: Investigations in relation to environmental information in the glacial system in Mt. Yulong,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
105
0
9

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(117 citation statements)
references
References 2 publications
3
105
0
9
Order By: Relevance
“…1) is in accord with global trends (1) and with other studies focused on this area of the eastern Himalaya (20,21,34,35). The lack of significant directional change in Rhododendron flowering time over this warming period might initially suggest that the genus is nonresponsive to temperature.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…1) is in accord with global trends (1) and with other studies focused on this area of the eastern Himalaya (20,21,34,35). The lack of significant directional change in Rhododendron flowering time over this warming period might initially suggest that the genus is nonresponsive to temperature.…”
Section: Discussionsupporting
confidence: 87%
“…Rapid temperature increases and changes in precipitation, in combination with the importance of Himalayan snowpack and glaciers to water supply and monsoon cycles, make the region one of the most threatened nonpolar areas of the world (1,19). Recent climate change is impacting Himalayan biological systems, including those upon which humans rely (20)(21)(22)(23).…”
mentioning
confidence: 99%
“…Minimum temperatures are particularly important in limiting the poleward (see Glossary) expansion of plant species, whereas limited water availability interacts with high temperatures to exert a direct climatic limitation on their expansion in the opposite, or equatorial, direction in many regions [1][2][3][4][5][6][7]. Changes in climate are, therefore, predicted to alter the geographic distribution of plant species at global to local scales.Contemporary plant range shifts are most frequently reported from mountain regions, with elevational shifts of the mountain treeline being the most commonly documented response to increasing temperatures [8][9][10][11][12]. The distributions of species in mountain regions are typically restricted to relatively narrow and well-delineated altitudinal bands, in comparison with often broad and poorly defined latitudinal distributions in the lowlands.…”
mentioning
confidence: 99%
“…Contemporary plant range shifts are most frequently reported from mountain regions, with elevational shifts of the mountain treeline being the most commonly documented response to increasing temperatures [8][9][10][11][12]. The distributions of species in mountain regions are typically restricted to relatively narrow and well-delineated altitudinal bands, in comparison with often broad and poorly defined latitudinal distributions in the lowlands.…”
mentioning
confidence: 99%
“…In mountainous areas, global climate change is manifested by a series of effects: the fragility related to mountain glacier shrinkage that characterizes high-altitude ecosystems (Haugland and Beatty, 2005;Baker and Moseley, 2007;Hodson et al, 2008), natural hazards (Richardson and Reynolds, 2000;Fischer et al, 2006;Huggel, 2009), and watershed hydrology (Immerzeel et al, 2010 [add to reference list]; Kaser et al, 2010;Liu et al, 2010;Gain et al, 2011 [add to reference list]; Schaner et al, 2012;Sorg et al, 2012). In recent years, many studies have reported increased glacier loss from various mountainous regions across the world (Oerlemans, 1994(Oerlemans, , 2005Bolch et al, 2012;Pathak, 2012;Sorg et al, 2012;Yao et al, 2012).…”
Section: Introductionmentioning
confidence: 99%